DEVELOPING SOCIAL INTELLIGENCE SCALE INSTRUMENTS FOR VOCATIONAL SCHOOL (SMK) STUDENTS - Tjalla, Awaluddin (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
AbstractThis study aims to develop scale instruments that can be used to identify potentials in relation to the readiness of students to enter the workforce with very high commissioning characteristics. The study was conducted at SMK Negeri 57 South Jakarta, using a simple random technique for 135 students. Data were analyzed using a Confirmatory Factor Analysis (CFA) with the SEM (Structural Equation Modeling) method. The findings of the study show that: (1) Steps to develop a valid and reliable social intelligence scale instrument are; synthesis, construct, type of instrument, instrument lattice, instrument items, theoretical validation, trial, calculate validity and reliability, instrument assembly. (2) The dimensions and indicators underlying the concept of social intelligence scale are; component of social awareness (dimensions of basic empathy, dimensions of alignment, empathic accuracy, social understanding), components of social facilities (dimensions of synchronization, self-appearance, influence, concern). (3) Calculation of instrument validity using total gain correlation formula, Pearson product moment with a significance level of 0.05; r table = 0.176. (4) Instrument reliability is α = 0.858.AbstrakPenelitian ini bertujuan untuk mengembangkan instrumen skala yang dapat digunakan untuk mengidentifikasi potensi dalam relasinya dengan kesiapan siswa untuk memasuki dunia kerja dengan karakteristik commissioning yang sangat tinggi. Penelitian dilakukan di SMK Negeri 57 Jakarta Selatan, menggunakan teknik acak sederhana untuk 135 siswa. Data dianalisis menggunakan Confirmatory Factor Analysis (CFA) dengan metode SEM (Structural Equation Modeling). Temuan penelitian menunjukkan bahwa: (1) Langkah-langkah untuk mengembangkan instrumen skala kecerdasan sosial yang valid dan dapat diandalkan adalah; sintesis, konstruk, jenis instrumen, instrumen kisi, item instrumen, validasi teoretis, percobaan, menghitung validitas dan reliabilitas, perakitan instrumen. (2) Dimensi dan indikator yang mendasari konsep skala kecerdasan sosial adalah; komponen kesadaran sosial (dimensi empati dasar, dimensi keselarasan, akurasi empatik, pemahaman sosial), komponen fasilitas sosial (dimensi sinkronisasi, penampilan diri, pengaruh, kepedulian). (3) Perhitungan validitas instrumen menggunakan rumus korelasi total gain, Pearson product moment dengan tingkat signifikansi 0,05; r tabel = 0,176. (4) Keandalan instrumen adalah α = 0,858.How to Cite : Tjalla, A. (2018). Developing Social Intelligence Scale Instruments for Vocational School (SMK) Students. TARBIYA: Journal of Education in Muslim Society, 5(2), 145-154. doi:10.15408/tjems.v5i2.10622.